Functional and Conceptual Differences of Micro-credit and Microfinance in Nepal - Dhakal, Chandra (Journal of Development Review, 2020)
The study analyzes the functional and conceptual differences between micro-credit and microfinance in Nepal. The main concern of this paper is to analyze the fundamental differences between the concept of microcredit and microfinance. Generally, it uses similar terminology; however, it has certain fundamental dissimilarity on a practical level. The main focus of this study is to analyze theoretically and conceptually differences the terms used in the field of economic development and poverty alleviation field. The study has been based on a qualitative research paradigm and only secondary sources of data were used for this study. Books, articles, thesis, dissertations, and reports were the main secondary source of data. Secondary information has collected through the library research method. Data were analyzed by using a simple paragraph description. The conclusion of this study has been drawn based on analysis and description.